Influência do aumento energético proveniente de dieta hiperlipídica na disfunção cardíaca em ratos com estenose aórtica supravalvar: participação das cadeias pesadas de miosina e da bomba de cálcio do retículo sarcoplasmático - Tomasi, Loreta Casquel De [UNESP] (2013)
Cardiac remodeling (CR) occurs in response to some cardiac injuries, such as pressure overload, and it may be manifested as changes in size, shape and function of the heart. In the model of supravalvar aortic stenosis (SVAS), echocardiographic studies performed in our laboratory showed that, 2 and 6 weeks post SVAS induction, rats developed left ventricular hypertrophy, diastolic dysfunction and improved systolic function. After 12 weeks there is systolic dysfunction and around the 20th week signs of heart failure appear. Several factors could contribute to the dysfunction in this experimental model, such as changes in protein expression of sarcoplasmic reticulum calcium ATPase (SERCA2a) and myosin heavy chain (MyHC), both with high ATPase capacity. Pathological CR is underscored by a reduction in fatty acid beta oxidation, which may cause energy deficit to the hypertrophied cardiac muscle. The aim of this work was to test the hypothesis that increased energy supply, derived from high-fat diet, attenuates cardiac dysfunction in the SVAS model. The mechanisms involved in the attenuation of dysfunction are related to decreased V1(α) to V3(β) MyHC isoform transition and increased SERCA2a/PLB ratio. Male Wistar rats, aged 21 days, were separated into two groups: operated control (Sham) and supravalvar aortic stenosis (SVAS). Six weeks after surgery, the animals were redistributed into four groups (n=12/group): fed with normolipidic diet (Sham-N and SVAS-N) or high-fat diet (Sham-H and SVAS-H). The nutritional profile was determined by food and calorie intake, feed efficiency, weight and body fat, adiposity index, blood glucose, triacylglycerol and non-esterified free fatty acid. The CR was characterized by analyses of the cardiac structure and function by echocardiogram in the 6th and 18th week, macroscopic study, energy metabolism and SERCA2a/PLB and β/α MyHC cardiac ratios. For comparisons between Sham and SVAS we used Student t test ...